Analisis Rasio Kesehatan Keuangan Dana Tabarru' Yang Mempengaruhi Profitabilitas Pada Asuransi Syariah di Indonesia (Periode 2012-2014) - Estiningtyas Kusuma Safitri; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The purpose of this research is to find out the effect of tabarru’ fund financial health towards the profitability in insurance. The method that used in this research is quantitative method and also using secondary data which obtained from financial reports and other reports started from 2012 until the end of 2014. The choosing of sample was done using sampling purposive method and there are 28 Islamic insurances that comply with the specified sample criteria. Analysis technique used is multiple linier regression analysis of panel data. The result are risk based capital that have significant level less than 0,1 but liquidity ratio, balance investment liability ratio, investment income ratio, claim expenses ratio, and tabarru’ fund change risk do not significantly influence the profitability of Islamic insurance companies because the significantly level more than 0,1.